Hubungan Ketuban Pecah Dini, Umur Kehamilan Dan Partus Lama Dengan Kejadian Asfiksia Neonatorum - Febrianti, Violita Eka; Veronica, Septika Yani; Kameliawati, Feri; Sulistiawati, Yuni (Wellness And Healthy Magazine, 2021)
Based on the data in 2019, out of 29,322 child mortality, 69% of them occurred during the neonatal period. The causes of neonatal mortality included LBW 35.3%, 27.0% Asphyxia, 23.1% congenital abnormalities, 12.5% Sepsis, 3.5% Tetanus neonatorum and 0.3% others. Neonatorum Asphyxia is a condition in which a baby is born who does not cry immediately after birth. Neonatorum Asphyxia is a neonatal emergency because it can cause hypoxia and brain damage. The high risk of experiencing Neonatorum Asphyxia is premature rupture of membranes, gestational age and prolonged labor. The purpose of this research was to determine the correlation between premature rupture of membranes, gestational age and prolonged labor with neonatorum asphyxia incidence at Mother and Child Hospital of Anugrah Medical Centre Metro City in 2020. This type of research is quantitative by applying an analytical design with a case-control approach. This research was conducted from February 1 to February 10, 2021, at the Mother and Child Hospital of Anugrah Medical Center Metro City. The sample in this research were 95 data of the babies. The sampling ratio in this study was 1: 1 where 1 was for the case sample and 1 for the control sample. The sampling technique used random sampling. The data analysis used the chi-square test. The analysis result using the chi-square test was found in the premature rupture of membranes variable with p-value = 0,000, the variable of old partus with a p-value of 0,000 and the variable of gestational age with p-value = 0.017 (less than 0.05), which means that there was a relationship between premature rupture of membranes, prolonged labor and gestational age with neonatorum asphyxia incidence at Mother and Child Hospital of Anugrah Medical Centre Metro City. This research is expected to be a policymaker as a consideration material, information and decision making for the management of newborns with neonatorum asphyxia.